Rab6 regulates transport and targeting of exocytotic carriers - Grigoriev, Ilya; Splinter, Daniël; Keijzer, Nanda; Wulf, Phebe S; Demmers, Jeroen; Ohtsuka, Toshihisa; Modesti, Mauro; Maly, Ivan V; Grosveld, Frank; Hoogenraad, Casper C; Akhmanova, Anna (Developmental cell, 2007)
Constitutive exocytosis delivers newly synthesized proteins, lipids, and other molecules from the Golgi apparatus to the cell surface. This process is mediated by vesicles, which bud off the trans-Golgi network, move along cytoskeletal filaments, and fuse with the plasma membrane. Here, we show that the small GTPase Rab6 marks exocytotic vesicles and, together with the microtubule plus-end-directed motor kinesin-1, stimulates their processive microtubule-based transport to the cell periphery. Furthermore, Rab6 directs targeting of secretory vesicles to plasma-membrane sites enriched in the cortical protein ELKS, a known Rab6 binding partner. Our data demonstrate that although Rab6 is not essential for secretion, it controls the organization of exocytosis within the cellular space.